Negative impact of daily screen use on inhibitory control network in preadolescence: A two-year follow-up study - Ya-Yun Chen; Hyungwook Yim; Tae-Ho Lee (Developmental Cognitive Neuroscience, 2023)
The COVID-19 pandemic has made an unprecedented shift in children’s daily lives. Children are increasingly spending time with screens to learn and connect with others. As the online environment rapidly substitutes in-person experience, understanding children’s neuropsychological trajectories associated with screen experiences is important. Previous findings suggest that excessive screen use can lead children to prefer more immediate rewards over delayed outcomes. We hypothesized that increased screen time delays a child’s development of inhibitory control system in the brain (i.e., fronto-striatal circuitry). By analyzing neuropsychological data from 8324 children (9–11ys) from the ABCD Study, we found that children who had more screen time showed a higher reward orientation and weaker fronto-striatal connectivity. Importantly, we found that the daily screen exposure mediated the effect of reward sensitivity on the development of the inhibitory control system in the brain over a two year period. These findings suggest possible negative long-term impacts of increased daily screen time on children’s neuropsychological development. The results further demonstrated that screen time influences dorsal striatum connectivity, which suggests that the effect of daily screen use is a habitual seeking behavior. The study provides neural and behavioral evidence for the negative impact of daily screen use on developing children.